The Role of Social Alliances in the Process of Reconstruction in Salgar, Colombia - Díaz Ramírez, Julia Helena (2022)
After a disaster partially destroyed the city of Salgar (Colombia) in 2015, a governance structure based on co-responsibility between public, private, and non-profit stakeholders was key in the reconstruction process. Three aspects of these alliances, identified from the theory, and their role in the construction of the common good are analyzed. Qualitative methods are applied, with an exploratory and interpretive approach to analyze both primary and secondary sources. In Salgar, the alliances between organizations from the three sectors allowed to: (a) manage primary uncertainty, while learning about opportunistic behavior and responses to it; (b) legitimize actions during the disaster response, and (c) build trust among stakeholders. The results suggest that the participation of organizations from the three sectors around an agreement of co-responsibilities facilitates both response in disaster situations and joint management with public organizations. Therefore, social alliances in reconstruction processes facilitate the management of scarce resources, stakeholder coordination, and the establishment of trust between beneficiaries and institutions.